A method for producing a polyimide thick film
Patent Information
- Application Number
- CN202511854781.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-10
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2045-12-10
AI Technical Summary
[0003]本发明所要解决的技术问题在于:提供一种聚酰亚胺厚膜的制备方法,解决现有方法生产效率较低或产品质量不佳等问题,实现使聚酰亚胺厚膜溶剂挥发更为顺利等技术效果,进而能够实现聚酰亚胺厚膜大幅宽高车速的连续性生产
本发明的一种聚酰亚胺厚膜的制备方法实现了厚度在125μm以上的聚酰亚胺厚膜能够以较大幅宽、较高车速连续生产,且产品的机械性能优异。其中,树脂通过共挤流出,形成双层结构,表层(上层)与芯层(下层)相比,表层树脂不添加亚胺化试剂,因此其亚胺化速率会慢于芯层,胶膜表面固化慢,再加上表层树脂粘度低,更有利于芯层树脂中的溶剂向上挥发;进一步将温度设置为表层树脂的温度低于芯层,更有助于相对延缓其固化;树脂流延至钢带后,钢带上表面加热温度低于下表面,也能够进一步使膜料内部的溶剂顺利挥发出来;因为人为使表层树脂固化减慢,故上层流延段的第一段烘箱采用小风速的平行风,上层其余烘箱采用斜吹风,可防止膜面起皱,后面的烘箱可采用大风速的垂直风,有利于胶膜整体的热固化;以上措施主要都是为了解决在溶剂挥发过程中,聚酰胺酸树脂的表面先于内部固化,致使内部的溶剂排出不畅的问题;另一方面,本发明在胶膜剥离后,溶剂含量较常规厚度薄膜更高,且采用先收缩后拉伸的横拉方式,与常规的先拉伸再收缩的方式相比,目的在于防止厚膜拉伸过程中断裂;开始时胶膜强度不够且自重较大,故先收缩,待接近完全亚胺化,有了较大机械强度后,再进行拉伸。
Smart Images

Figure CN121468996B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polyimide film manufacturing technology, and specifically relates to a method for preparing a polyimide thick film. Background Technology
[0002] Polyimide (PI) films possess excellent thermal, mechanical, and electrical insulation properties, and are widely used in microelectronics, rail transportation, aerospace, and other fields. With the continuous development of science and technology, the requirements for PI film thickness are becoming increasingly stringent, leading to a growing demand for ultra-thin and ultra-thick PI films. However, producing PI thick films, such as those greater than 125 μm, presents numerous challenges in actual production. For example, compared to thin films, a large amount of solvent needs to be evaporated, resulting in slower production speeds, typically ≤3 m / min. Furthermore, during solvent evaporation, the surface of the polyamic acid resin cures before the interior, hindering solvent drainage and causing air bubbles, delamination, edge warping, and even detachment from the steel belt. During transverse stretching, the significant weight of the thick film makes it prone to edge breakage, resulting in narrower film widths, typically ≤1 m. In summary, the overall production efficiency of polyimide thick films is currently low. Summary of the Invention
[0003] The technical problem to be solved by the present invention is to provide a method for preparing polyimide thick film, which solves the problems of low production efficiency or poor product quality of existing methods, and achieves technical effects such as smoother solvent evaporation of polyimide thick film, thereby enabling continuous production of polyimide thick film with large width, high speed and high capacity.
[0004] According to the technical solution of the present invention, the present invention provides a method for preparing a polyimide thick film, comprising the following steps: Step S1: Prepare polyamic acid resin; add diamine monomer and dianhydride monomer to solvent in sequence, and after polycondensation reaction, obtain a first polyamic acid resin and a second polyamic acid resin with different viscosities, the viscosity of the first polyamic acid resin is higher than that of the second polyamic acid resin. Step S2: Add a chemical imidizing agent to the first polyamic acid resin and mix evenly to obtain a mixed resin. Then, send the mixed resin and the second polyamic acid resin to the two channels of the double-layer co-extrusion die for double-layer co-extrusion. The mixed resin and the second polyamic acid resin are cast onto the steel strip to form a double-layer structure, with the mixed resin in contact with the surface of the steel strip and the second polyamic acid resin located on the surface of the mixed resin. Then, heat in an oven to obtain a polyimide film. Step S3: After peeling off the polyimide film, stretch it laterally, then anneal and cut it to obtain a polyimide thick film of the required size.
[0005] In some embodiments, in step S1, the viscosity of the first polyamic acid resin is 300,000 to 400,000 cP, and the viscosity of the second polyamic acid resin is 100,000 to 200,000 cP. And / or, in step S1, the solid content of the polyamic acid resin is set to 25% to 40%, and the molar ratio of diamine monomer to dianhydride monomer in the polyamic acid resin is 1:(0.8 to 1.2).
[0006] In some embodiments, in step S1, the solvent is one or more combinations of N,N'-dimethylformamide, N,N'-dimethylacetamide, and N-methylpyrrolidone; the diamine monomer is at least one of aromatic diamines; and the dianhydride monomer is at least one of aromatic dianhydrides. And / or, in step S2, the chemical imidizing agent is composed of an organic acid anhydride dehydrating agent and an organic base catalyst; the organic acid anhydride dehydrating agent includes one or more of acetic anhydride, propionic anhydride, butyric anhydride, benzoic anhydride, and maleic anhydride; the organic base catalyst includes one or more of isoquinoline, pyridine, 2-methylpyridine, and 3-methylpyridine; wherein, the molar ratio of the organic acid anhydride dehydrating agent to dianhydride molecules is (1-8):1; the molar ratio of the organic base catalyst to dianhydride molecules is (0.1-6):1.
[0007] In some embodiments, during step S2, when the mixed resin and the second polyamic acid resin are respectively fed into the two channels of the double-layer co-extrusion die, the temperature of the mixed resin is 0°C to 5°C and the temperature of the second polyamic acid resin is -5°C to 0°C when it flows into the die.
[0008] In some embodiments, in step S2, the thickness of the mixed resin in the double-layer structure cast onto the steel strip accounts for 3 / 4 to 4 / 5 of the total thickness of the double-layer structure.
[0009] In some embodiments, in step S2, after the resin is cast onto the steel strip, hot air heating is provided on both the upper and lower surfaces of the steel strip. The surface in contact with the air, i.e. the upper surface of the steel strip, is heated at a temperature 3°C to 10°C lower than the heating temperature on the back side of the steel strip.
[0010] In some embodiments, the steel strip passes through the oven of the casting machine, the oven of the casting machine comprising multiple sections arranged sequentially along the running direction of the steel strip, and each section of the oven is provided with an air outlet nozzle. In step S2, after the film is cast onto the steel strip, the double-layer structure is first located in the first oven section, the length of which is 1 / 3 to 1 / 2 of the total length of the upper casting section. The first oven section uses hot air parallel to the film surface for heating, with the air velocity at the outlet nozzles being 0.5 m / s to 4 m / s. The remaining oven sections of the upper casting section use hot air at an angle of 30° to 45° to the film surface, with the air velocity at the outlet nozzles being 4 m / s to 8 m / s. The lower casting section uses hot air perpendicular to the film surface in each of its oven sections, with the air velocity at the outlet nozzles being 8 m / s to 15 m / s.
[0011] In some embodiments, in step S3, the solvent content of the peeled polyimide film is 40% to 70%.
[0012] In some embodiments, during the transverse stretching in step S3, the polyimide film shrinks during the high-temperature process. Assuming the width at the inlet is 1d, the width at 1 / 3 of the total length of the transverse stretching section is 0.95d to 0.99d, and the width at the outlet is 1d to 1.05d.
[0013] In some embodiments, the final thickness of the polyimide thick film is 125 μm to 225 μm, and the width is 1 m to 2.5 m; the mechanical properties are: modulus ≥ 5 GPa, tensile strength ≥ 450 MPa, and elongation at break ≥ 60%; And / or, the production speed for polyimide thick film fabrication is 1 m / min to 6 m / min.
[0014] Compared with the prior art, the beneficial technical effects of the present invention are as follows: This invention discloses a method for preparing polyimide thick films, enabling continuous production of polyimide thick films with a thickness of 125 μm or more at a relatively large width and high speed, while producing products with excellent mechanical properties. The resin is co-extruded to form a double-layer structure. Compared to the core layer (lower layer), the surface layer resin does not contain imidizing agents, resulting in a slower imidization rate and slower curing of the film surface. Furthermore, the lower viscosity of the surface layer resin facilitates the upward evaporation of solvents from the core layer resin. Setting the temperature of the surface layer resin lower than that of the core layer further delays its curing. After the resin is cast onto the steel belt, the heating temperature of the upper surface of the steel belt is lower than that of the lower surface, further promoting the evaporation of solvents from the film material. Because the curing of the surface layer resin is intentionally slowed down, the first section of the upper layer casting oven uses a low-speed parallel airflow, while the remaining sections of the upper layer... The oven uses oblique airflow to prevent wrinkling of the film surface, and the rear oven can use high-speed vertical airflow, which is beneficial to the overall thermal curing of the film. The above measures are mainly to solve the problem that the surface of the polyamic acid resin cures before the inside during solvent evaporation, resulting in poor solvent discharge from the inside. On the other hand, after the film is peeled off, the solvent content is higher than that of conventional thick films, and a horizontal stretching method of shrinking before stretching is used. Compared with the conventional method of stretching before shrinking, the purpose is to prevent the film from breaking during the stretching process. At the beginning, the film strength is not enough and its weight is large, so it is shrunk first. After it is nearly fully imidized and has greater mechanical strength, it is stretched. Attached Figure Description
[0015] Figure 1 This is a flowchart of the method provided by the present invention.
[0016] Figure 2 This is a schematic diagram of the casting machine used in the embodiments of the present invention.
[0017] Explanation of reference numerals in the attached figures: 1. Die head; 2. Steel belt; 3. First drying oven; 4. First drum; 5. Second drum; 6. Peeling roller. Detailed Implementation
[0018] This invention provides a method for preparing polyimide thick films, solving the problems of low production efficiency or poor product quality in existing methods. The invention involves a polyamic acid resin obtained by the polycondensation reaction of diamine and dianhydride, which is then cast onto a steel strip, peeled off, stretched laterally, and annealed and slit to obtain the polyimide thick film. By controlling the resin viscosity, adding an imidizing agent, and further optimizing and controlling the casting and drying processes, the invention achieves better solvent evaporation in the polyimide thick film, enabling continuous production of films with a wide width, height, and speed range, for example, from 150μm to 200μm, while producing products with excellent mechanical properties.
[0019] Please see Figure 1 The present invention provides a method for preparing a polyimide thick film, comprising the following steps.
[0020] Step S1: Prepare polyamic acid (PAA) resin; add diamine monomer and dianhydride monomer to solvent in sequence, and after polycondensation reaction, obtain a first polyamic acid resin and a second polyamic acid resin with different viscosities, the viscosity of the first polyamic acid resin is higher than that of the second polyamic acid resin.
[0021] Step S2: Add a chemical imidizing agent to the first polyamic acid resin and mix evenly to obtain a mixed resin. Then, send the mixed resin and the second polyamic acid resin to the two channels of the double-layer co-extrusion die for double-layer co-extrusion. The mixed resin and the second polyamic acid resin are cast onto the steel strip to form a double-layer structure, with the mixed resin in contact with the surface of the steel strip and the second polyamic acid resin located on the surface of the mixed resin. Then, heat in an oven to obtain a polyimide film.
[0022] Step S3: After peeling off the polyimide film, stretch it laterally, then anneal and cut it to obtain a polyimide thick film of the required size.
[0023] Preferably, in step S1, the viscosity of the first polyamic acid resin is 300,000 to 400,000 cP, and the viscosity of the second polyamic acid resin is 100,000 to 200,000 cP. The formulations of the first and second polyamic acid resins are the same, only their viscosities differ.
[0024] Preferably, in step S1, the solid content of the polyamic acid resin (including the first polyamic acid resin and the second polyamic acid resin) is set to 25% to 40%, more preferably 28% to 35%. The molar ratio of diamine monomer to dianhydride monomer in the polyamic acid resin (including the first polyamic acid resin and the second polyamic acid resin) is 1:(0.8 to 1.2), more preferably 1:1.
[0025] Preferably, in step S1, the solvent is one or more combinations of N,N'-dimethylformamide, N,N'-dimethylacetamide, and N-methylpyrrolidone. The diamine monomer is at least one of aromatic diamines, more preferably at least one of p-phenylenediamine, 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl sulfone, 4,4'-diaminobenzophenone, and 3,4'-diaminodiphenyl ether. The dianhydride monomer is at least one of aromatic dianhydrides, more preferably at least one of pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-diphenyl ether tetracarboxylic dianhydride, and 3,3',4,4'-benzophenone tetracarboxylic dianhydride.
[0026] Preferably, in step S2, the chemical imidizing agent consists of an organic acid anhydride dehydrating agent and an organic base catalyst. The organic acid anhydride dehydrating agent includes one or more of acetic anhydride, propionic anhydride, butyric anhydride, benzoic anhydride, and maleic anhydride (mixtures formed in any proportion). The organic base catalyst includes one or more of isoquinoline, pyridine, 2-methylpyridine, and 3-methylpyridine (mixtures formed in any proportion). The molar ratio of the organic acid anhydride dehydrating agent to dianhydride molecules is (1–8):1, more preferably (2–6):1. The molar ratio of the organic base catalyst to dianhydride molecules is (0.1–6):1, more preferably (0.3–4):1.
[0027] Preferably, in step S2, during the process of feeding the mixed resin and the second polyamic acid resin into the two channels of the double-layer co-extrusion die, the temperature of the mixed resin is 0℃~5℃ and the temperature of the second polyamic acid resin is -5℃~0℃ when flowing into the die.
[0028] Preferably, in step S2, the thickness of the mixed resin in the double-layer structure cast onto the steel strip accounts for 3 / 4 to 4 / 5 of the total thickness of the double-layer structure.
[0029] Preferably, in step S2, after the resin is cast onto the steel strip, hot air heating is provided on both the upper and lower surfaces of the steel strip. The surface of the resin in contact with the air (film surface) is the upper surface of the steel strip. The heating temperature of the upper surface of the steel strip is 3°C to 10°C lower than the heating temperature of the back surface of the steel strip, and more preferably 5°C to 8°C lower.
[0030] Preferably, the steel strip passes through the oven of the casting machine. The oven of the casting machine includes multiple sections arranged sequentially along the running direction of the steel strip, and each section of the oven is equipped with an air outlet nozzle. In step S2, after casting onto the steel strip, the double-layer structure is initially located in the first section of the oven, the length of which is 1 / 3 to 1 / 2 of the total length of the upper casting section. The first section of the oven uses hot air parallel to the film surface for heating (the air direction can be the same as the resin movement direction), and the air velocity at the air outlet nozzles in the first section of the oven is 0.5 m / s to 4 m / s, more preferably 1 m / s to 3 m / s. In the upper casting section (outside the first oven), the remaining ovens use hot air heated at an angle of 30° to 45° to the film surface (0° is parallel to the film surface; this 30° to 45° angle is between parallel and perpendicular; the airflow component in the resin movement direction can be the same as the resin movement direction). The air velocity at the outlet nozzles in the remaining ovens of the upper casting section is 4 m / s to 8 m / s, more preferably 5 m / s to 7 m / s. In each section of the lower casting section, the ovens use hot air heated perpendicular to the film surface. The air velocity at the outlet nozzles in each section of the lower casting section is 8 m / s to 15 m / s, more preferably 10 m / s to 13 m / s.
[0031] More specifically, please refer to Figure 2An embodiment of the present invention provides a casting machine comprising a first drum 4, a second drum 5, and an annular steel belt 2 drivenly connected to the first drum 4 and the second drum 5. A die head 1 is disposed above the first drum 4. The die head 1 is a double-layer co-extrusion die head. The movement direction of the first drum 4 is shown by the arrow in the figure. The annular steel belt 2 has an upper straight section and a lower straight section. The oven is correspondingly provided with upper and lower layers, namely an upper casting section and a lower casting section. The casting section refers to the section where the resin is cast to the annular steel belt and finally peeled off. At least two sections of the oven are provided in both the upper and lower layers. Figure 2 In the illustrated embodiment, the upper casting section is a three-section oven located above, and the lower casting section is a three-section oven located below. The film material (mixed resin and second polyamic acid resin, hereinafter referred to as resin) is extruded from the die head 1 onto the steel belt 2 above the first drum 4. Then, as the steel belt 2 moves to the left in the figure, it first enters the first oven 3 for the aforementioned "parallel air" process, and then sequentially enters the remaining oven sections for the aforementioned "oblique air" and "vertical air" processes. After the film material has traveled nearly one revolution with the steel belt 2, it is peeled off by the peeling roller. It can be understood that... Figure 2 This is for illustrative purposes only; the actual structure also includes exhaust vents. The temperature, velocity, and direction of the hot air can vary in each section of the drying oven, determined by design calculations. Temperature and velocity control, as well as the structure of the air box and exhaust nozzles, are easily achievable using existing technology, or other feasible methods can be employed to achieve the desired effect. The focus of this section is on using this multi-stage drying method with specific airflow directions. This invention is not limited to this; other types of casting machines can also apply or be modified to utilize the methods of this invention.
[0032] Preferably, in step S3, the solvent content of the peeled polyimide film is 40% to 70%, more preferably 50% to 60%. The solvent content is calculated as follows: solvent content = (m1 - m2) / m1; where m1 is the mass of the polyimide film, and m2 is the dry film mass, which is obtained, for example, by drying the polyimide film in an oven at 450°C for 0.5 hours.
[0033] Preferably, in step S3, during the transverse stretching process, the polyimide film shrinks due to the high temperature. Assuming the width at the inlet is 1d, the width at one-third of the total length of the transverse stretching section is 0.95d to 0.99d, and the width at the outlet is 1d to 1.05d. It should be noted that this method uses high-temperature transverse stretching, which involves shrinkage before stretching. The film shrinks simultaneously during conveying and stretching in the high-temperature environment of the transverse stretching machine. Therefore, even if the width narrows compared to the inlet during stretching, there is still a significant transverse stretching effect. The transverse stretching section refers to the distance the polyimide film is stretched laterally, from the stretching inlet to the stretching outlet.
[0034] Preferably, after step S3, the final thickness of the polyimide thick film is 125μm to 225μm, more preferably 150μm to 200μm; the width is 1m to 2.5m, more preferably 1.2m to 2.2m; and the mechanical properties are: modulus ≥ 5GPa, tensile strength ≥ 450MPa, and elongation at break ≥ 60%.
[0035] Preferably, the production speed of the polyimide thick film forming machine is 1 m / min to 6 m / min, and more preferably 3 m / min to 5 m / min. The production speed refers to the speed at which the polyimide thick film is produced after step S3. Compared with the prior art, this solution can achieve a higher production speed while ensuring that the quality of the thick film meets or exceeds the requirements.
[0036] The principles and beneficial effects of this invention are as follows.
[0037] In this invention, the resin is co-extruded to form a double-layer structure. Compared to the core layer (lower layer), the surface layer (upper layer) resin does not contain imidizing agents, therefore its imidization rate is slower than that of the core layer. This results in slower curing of the film surface. Furthermore, the lower viscosity of the surface layer resin facilitates the upward evaporation of solvent from the core layer resin. Setting the temperature of the surface layer resin lower than that of the core layer further helps to relatively delay its curing. Similarly, after the resin is cast onto the steel belt, the heating temperature of the upper surface of the steel belt is lower than that of the lower surface, which further facilitates the evaporation of solvent from the film material. Because the curing of the surface layer resin is intentionally slowed down, the first section of the upper casting stage uses a low-speed parallel airflow, while the remaining upper ovens use oblique airflow to prevent wrinkling of the film surface. The subsequent ovens can use a high-speed vertical airflow, which is beneficial for the overall thermal curing of the film. These measures are mainly to address the problem that during solvent evaporation, the surface of the polyamic acid resin cures before the interior, hindering the drainage of the internal solvent.
[0038] On the other hand, after the adhesive film is peeled off, the solvent content of the present invention is higher than that of conventional thick films, and a transverse stretching method of shrinking first and then stretching is adopted. Compared with the conventional method of stretching first and then shrinking, the purpose is to prevent the thick film from breaking during the stretching process. At the beginning, the adhesive film is not strong enough and has a large weight, so it is shrunk first. After it is nearly fully imidized and has greater mechanical strength, it is stretched.
[0039] The following description, in conjunction with specific embodiments, provides further details.
[0040] Example 1: Step S1: Prepare polyamic acid (PAA) resin by sequentially adding diamine monomer and dianhydride monomer to a solvent. After polycondensation, a first polyamic acid resin A and a second polyamic acid resin B with different viscosities are obtained. Step S2: Add a chemical imidizing agent to resin A and mix thoroughly. Then, feed the two resins separately into the two channels of a double-layer co-extrusion die. The resin A, mixed with the chemical imidizing agent, is cast onto a steel strip, with resin B on the surface of resin A. The mixture is then heated in an oven to obtain a polyimide (PI) film. Step S3: After peeling off the PI film, perform high-temperature transverse stretching, followed by annealing and slitting to obtain a thick polyimide film.
[0041] In the preparation of PAA resin, the solvent is N,N'-dimethylformamide, the diamine monomers are p-phenylenediamine (PDA) and 4,4'-diaminodiphenyl ether (ODA), and the dianhydride monomer is pyromellitic dianhydride (PMDA). The molar ratio of PDA, ODA, and PMDA is 3:7:10. The solid content of the PAA resin is 25%, with resin A having a viscosity of 300,000 cP and resin B having a viscosity of 100,000 cP. When flowing into the die head, the temperature of resin A, mixed with the chemical imidizing agent, is 0°C, and the temperature of resin B is -5°C.
[0042] The chemical imidizing agent is composed of acetic anhydride and isoquinoline, wherein the molar ratio of acetic anhydride to PMDA in resin A is 2:1, and the molar ratio of isoquinoline to PMDA in resin A is 0.3:1. After casting, resin A mixed with the chemical imidizing agent accounts for 3 / 4 of the thickness of the entire PAA resin bilayer structure.
[0043] Hot air heating is provided on both the upper and lower surfaces of the steel strip, and the heating temperature of the upper surface, i.e. the film surface, is 3°C lower than that of the back surface of the steel strip.
[0044] After the PAA resin is cast onto the steel belt, the length of the first oven section is 1 / 3 of the total length of the upper casting section. The first oven section uses hot air parallel to the film surface for heating, with a nozzle air velocity of 1 m / s. The remaining ovens in the upper casting section use hot air at a 30° angle to the film surface, with an outlet nozzle air velocity of 4.5 m / s. The ovens in each section of the lower casting section use hot air perpendicular to (i.e. directly opposite) the film surface for heating, with an outlet nozzle air velocity of 10 m / s.
[0045] After the PAA resin is peeled off, the solvent content of the film is 50%.
[0046] During lateral stretching, the width ratio at the inlet, 1 / 3 stretching point, and outlet is 1:0.96:1.
[0047] The film-forming speed was 6 m / min, and the final polyimide film had a thickness of 130 μm, a width of 2.3 m, and mechanical properties of 5.5 GPa modulus, 472 MPa tensile strength, and 68% elongation at break.
[0048] Example 2: The film-forming steps are basically the same as in Example 1.
[0049] In the preparation of PAA resin, the solvent is N,N'-dimethylformamide, the diamine monomers are p-phenylenediamine (PDA) and 4,4'-diaminodiphenyl ether (ODA), and the dianhydride monomer is pyromellitic dianhydride (PMDA). The molar ratio of PDA, ODA, and PMDA is 3:7:10. The solid content of the PAA resin is 30%, with resin A having a viscosity of 350,000 cP and resin B having a viscosity of 120,000 cP. When flowing into the die head, the temperature of resin A, mixed with the chemical imidizing agent, is 3°C, and the temperature of resin B is -2°C.
[0050] The chemical imidizing agent is composed of acetic anhydride and isoquinoline, wherein the molar ratio of acetic anhydride to PMDA in resin A is 3:1, and the molar ratio of isoquinoline to PMDA in resin A is 1:1. After casting, the resin A mixed with the chemical imidizing agent accounts for 3 / 4 of the total thickness of the PAA resin.
[0051] Hot air heating is provided on both the upper and lower surfaces of the steel strip, and the heating temperature of the upper surface, i.e. the film surface, is 5°C lower than that of the back surface of the steel strip.
[0052] After the PAA resin is cast onto the steel belt, the length of the first oven section is 1 / 3 of the total length of the upper casting section. The first oven section uses hot air parallel to the film surface for heating, with a nozzle air velocity of 1.5 m / s. The remaining ovens in the upper casting section use hot air at a 35° angle to the film surface, with an outlet nozzle air velocity of 5 m / s. The ovens in the lower casting section all use hot air perpendicular to (i.e. directly opposite) the film surface for heating, with an outlet nozzle air velocity of 13 m / s.
[0053] After the PAA resin is peeled off, the solvent content of the film is 55%.
[0054] During lateral stretching, the width ratio at the inlet, 1 / 3 stretching point, and outlet is 1:0.99:1.02.
[0055] The film-forming speed was 4 m / min, and the final polyimide film had a thickness of 150 μm, a width of 2 m, and mechanical properties of: modulus 5.2 GPa, tensile strength 463 MPa, and elongation at break 70%.
[0056] Example 3: The film-forming steps are basically the same as in Example 1.
[0057] In the preparation of PAA resin, the solvent is N,N'-dimethylformamide, the diamine monomers are p-phenylenediamine (PDA) and 4,4'-diaminodiphenyl ether (ODA), and the dianhydride monomer is pyromellitic dianhydride (PMDA). The molar ratio of PDA, ODA, and PMDA is 3:7:10. The solid content of the PAA resin is 35%, with resin A having a viscosity of 380,000 cP and resin B having a viscosity of 150,000 cP. When flowing into the die head, the temperature of resin A, mixed with the chemical imidizing agent, is 4°C, and the temperature of resin B is -3°C.
[0058] The chemical imidizing agent is composed of acetic anhydride and isoquinoline, wherein the molar ratio of acetic anhydride to PMDA in resin A is 4:1, and the molar ratio of isoquinoline to PMDA in resin A is 2:1. After casting, the resin A mixed with the chemical imidizing agent accounts for 4 / 5 of the total thickness of the PAA resin.
[0059] Hot air heating is provided on both the upper and lower surfaces of the steel strip, and the heating temperature of the upper surface, i.e. the film surface, is 8°C lower than that of the back surface of the steel strip.
[0060] After the PAA resin is cast onto the steel belt, the length of the first oven section is 2 / 5 of the total length of the upper casting section. The first oven section uses hot air parallel to the film surface for heating, with a nozzle air velocity of 2 m / s. The remaining ovens in the upper casting section use hot air at a 40° angle to the film surface, with an outlet nozzle air velocity of 6 m / s. The ovens in the lower casting section all use hot air perpendicular to (i.e. directly opposite) the film surface for heating, with an outlet nozzle air velocity of 14 m / s.
[0061] After the PAA resin is peeled off, the solvent content of the film is 65%.
[0062] During lateral stretching, the width ratio at the inlet, 1 / 3 stretching point, and outlet is 1:0.98:1.
[0063] The film-forming speed was 3.5 m / min, and the final polyimide film had a thickness of 200 μm, a width of 1.6 m, and mechanical properties of 5.1 GPa modulus, 452 MPa tensile strength, and 63% elongation at break.
[0064] Example 4: The film-forming steps are basically the same as in Example 1.
[0065] In the preparation of PAA resin, the solvent is N,N'-dimethylformamide, the diamine monomers are p-phenylenediamine (PDA) and 4,4'-diaminodiphenyl ether (ODA), and the dianhydride monomer is pyromellitic dianhydride (PMDA). The molar ratio of PDA, ODA, and PMDA is 3:7:10. The solid content of the PAA resin is 40%, with resin A having a viscosity of 400,000 cP and resin B having a viscosity of 200,000 cP. When flowing into the die head, the temperature of resin A, mixed with the chemical imidizing agent, is 5°C, and the temperature of resin B is 0°C.
[0066] The chemical imidizing agent is composed of acetic anhydride and isoquinoline, wherein the molar ratio of acetic anhydride to PMDA in resin A is 6:1, and the molar ratio of isoquinoline to PMDA in resin A is 5:1. After casting, resin A mixed with the chemical imidizing agent accounts for 4 / 5 of the total thickness of the PAA resin.
[0067] Hot air heating is provided on both the upper and lower surfaces of the steel strip, and the heating temperature of the upper surface, i.e. the film surface, is 10°C lower than that of the back surface of the steel strip.
[0068] After the PAA resin is cast onto the steel belt, the length of the first oven section is 1 / 2 of the total length of the upper casting section. The first oven section uses hot air parallel to the film surface for heating, with a nozzle air velocity of 3.5 m / s. The remaining ovens in the upper casting section use hot air at a 45° angle to the film surface, with an outlet nozzle air velocity of 8 m / s. The ovens in each section of the lower casting section use hot air perpendicular to (i.e. directly opposite) the film surface for heating, with an outlet nozzle air velocity of 15 m / s.
[0069] After the PAA resin is peeled off, the solvent content of the film is 70%.
[0070] During lateral stretching, the width ratio at the inlet, 1 / 3 stretching point, and outlet is 1:0.98:1.05.
[0071] The film-forming speed was 3 m / min, and the final polyimide film had a thickness of 225 μm, a width of 1.2 m, and mechanical properties of 5.05 GPa, 453 MPa, and 62% elongation at break.
[0072] Comparative Example 1: The difference from Example 1 is that acetic anhydride and isoquinoline are also added to resin B. The molar ratio of acetic anhydride to PMDA in resin B is 2:1, and the molar ratio of isoquinoline to PMDA in resin B is 0.3:1.
[0073] The result was that the PI film delaminated and contained air bubbles.
[0074] Comparative Example 2: The difference from Example 2 is that the viscosity of PAA resin A is 350,000 cP and the viscosity of resin B is 300,000 cP.
[0075] The result was that the PI film delaminated and the edges were warped.
[0076] Comparative Example 3: The difference from Example 1 is that the molar ratio of acetic anhydride to PMDA in resin A is 0.5:1, and the molar ratio of isoquinoline to PMDA in resin A is 0.05:1.
[0077] The result was that stable winding of PI thick film was achieved, but the mechanical properties were poor: modulus 2.1 GPa, tensile strength 203 MPa, and elongation at break 30%.
[0078] Comparative Example 4: The difference from Example 3 is that after the PAA resin is cast onto the steel strip, there is no temperature difference between the upper and lower surfaces of the steel strip when heated.
[0079] The result was that a large number of air bubbles appeared inside the PAA film.
[0080] Comparative Example 5: The difference from Example 4 is that after the PAA film is peeled off, the solvent content of the film is 35%, and when stretched laterally, the width ratio of the inlet, the 1 / 3 stretching section, and the outlet is 1:1:1.06.
[0081] The result was that the PI film broke when stretched horizontally.
[0082] Comparative Example 6: The difference from Example 1 is that when the resin A mixed with the chemical imidizing agent flows into the die head, the temperature is 8°C and the temperature of the resin B is 3°C.
[0083] The result was that bubbles appeared on the surface of the PAA resin during the casting stage.
[0084] Comparative Example 7: The difference from Example 1 is that after the PAA resin is cast onto the steel belt, the length of the first oven section is 1 / 4 of the total length of the casting section, and the air velocity at the nozzle is 5 m / s. The remaining ovens in the upper casting section are heated with hot air at a 60° angle to the film surface, and the air velocity at the outlet nozzle is 4.5 m / s. In the lower casting section, each oven section is heated with hot air perpendicular to (i.e., directly opposite) the film surface, and the air velocity at the outlet nozzle is 17 m / s. The result was that the PAA resin surface wrinkled in the upper second stage oven, and the surface wrinkling became severe in the lower oven, eventually causing it to fall off the steel belt.
[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; obviously, the described embodiments are some embodiments of the present invention, but not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention; for ease of description, only the parts related to the invention are shown in the accompanying drawings. In the absence of conflict, the embodiments and features in the embodiments of the present invention can be combined with each other; modifications to the technical solutions described in the foregoing embodiments, or equivalent substitutions for some of the technical features, do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a polyimide thick film, characterized in that, The steel strip passes through the oven of the casting machine. The oven of the casting machine includes multiple sections arranged sequentially along the running direction of the steel strip, and each section of the oven is equipped with an air outlet nozzle. The method for preparing the polyimide thick film includes the following steps: Step S1: Prepare polyamic acid resin; add diamine monomer and dianhydride monomer to solvent in sequence, and after polycondensation reaction, obtain a first polyamic acid resin and a second polyamic acid resin with different viscosities. The viscosity of the first polyamic acid resin is higher than that of the second polyamic acid resin. Step S2: Add a chemical imidizing agent to the first polyamic acid resin and mix evenly to obtain a mixed resin. Then, send the mixed resin and the second polyamic acid resin to the two channels of the double-layer co-extrusion die for double-layer co-extrusion. The mixed resin and the second polyamic acid resin are cast onto the steel strip to form a double-layer structure, with the mixed resin in contact with the surface of the steel strip and the second polyamic acid resin located on the surface of the mixed resin. Then, heat in an oven to obtain a polyimide film. Step S3: After peeling off the polyimide film, stretch it laterally, then anneal and cut it to obtain a polyimide thick film of the required size. Furthermore, in step S2, during the process of feeding the mixed resin and the second polyamic acid resin into the two flow channels of the double-layer co-extrusion die, the temperature of the mixed resin when flowing into the die is 0℃~5℃, and the temperature of the second polyamic acid resin is -5℃~0℃; after being cast onto the steel strip, both the upper and lower surfaces of the steel strip are heated by hot air, and the heating temperature of the upper surface of the steel strip, which is the surface in contact with the air, is 3℃~10℃ lower than the heating temperature of the back surface of the steel strip; after being cast onto the steel strip, the double-layer structure is first located in the first section of the drying oven, the length of the first section of the drying oven is... The first section of the upper casting section is 1 / 3 to 1 / 2 of the total length. The first section of the oven uses hot air parallel to the film surface for heating, and the air velocity of the air nozzles in the first section of the oven is 0.5 m / s to 4 m / s. The remaining sections of the upper casting section use hot air at an angle of 30° to 45° to the film surface for heating, and the air velocity of the air nozzles in the remaining sections of the upper casting section is 4 m / s to 8 m / s. The lower casting section uses hot air perpendicular to the film surface for heating in each section of the oven, and the air velocity of the air nozzles in the lower casting section is 8 m / s to 15 m / s.
2. The method for preparing a polyimide thick film according to claim 1, characterized in that, In step S1, the viscosity of the first polyamic acid resin is 300,000 to 400,000 cP, and the viscosity of the second polyamic acid resin is 100,000 to 200,000 cP. And / or, in step S1, the solid content of the polyamic acid resin is set to 25% to 40%, and the molar ratio of diamine monomer to dianhydride monomer in the polyamic acid resin is 1:(0.8 to 1.2).
3. The method for preparing a polyimide thick film according to claim 1, characterized in that, In step S1, the solvent is one or more combinations of N,N'-dimethylformamide, N,N'-dimethylacetamide, and N-methylpyrrolidone; the diamine monomer is at least one of aromatic diamines; and the dianhydride monomer is at least one of aromatic dianhydrides. And / or, In step S2, the chemical imidizing agent is composed of an organic acid anhydride dehydrating agent and an organic base catalyst; the organic acid anhydride dehydrating agent includes one or more of acetic anhydride, propionic anhydride, butyric anhydride, benzoic anhydride, and maleic anhydride; the organic base catalyst includes one or more of isoquinoline, pyridine, 2-methylpyridine, and 3-methylpyridine; wherein, the molar ratio of the organic acid anhydride dehydrating agent to dianhydride molecules is (1-8):1; the molar ratio of the organic base catalyst to dianhydride molecules is (0.1-6):
1.
4. The method for preparing a polyimide thick film according to claim 1, characterized in that, In step S2, the thickness of the mixed resin in the double-layer structure cast onto the steel strip accounts for 3 / 4 to 4 / 5 of the total thickness of the double-layer structure.
5. The method for preparing a polyimide thick film according to claim 1, characterized in that, In step S3, the solvent content of the peeled polyimide film is 40% to 70%.
6. The method for preparing a polyimide thick film according to claim 1, characterized in that, In step S3, during the transverse stretching, the polyimide film shrinks during the high-temperature process. Assuming the width at the inlet is 1d, the width at 1 / 3 of the total length of the transverse stretching section is 0.95d to 0.99d, and the width at the outlet is 1d to 1.05d.
7. The method for preparing a polyimide thick film according to claim 1, characterized in that, The final thickness of the polyimide thick film is 125μm to 225μm, and the width is 1m to 2.5m; the mechanical properties are: modulus ≥5GPa, tensile strength ≥450MPa, and elongation at break ≥60%; And / or, the production speed for polyimide thick film fabrication is 1m / min to 6m / min.
Citation Information
Patent Citations
High barrier coextruded stretch film
CN102029754A
Preparation method of polyimide film
CN116731364A